Dip-pen patterning of poly(9,9-dioctylfluorene) chain-conformation-based nano-photonic elements - Perevedentsev, A; Sonnefraud, Y; Belton, CR; Sharma, S; Cass, AEG; Maier, SA; Kim, J-S; Stavrinou, PN; Bradley, DDC (Springer Nature, 2015)
Metamaterials are a promising new class of materials, in which sub-wavelength physical structures, rather than variations in chemical composition, can be used to modify the nature of their interaction with electromagnetic radiation. Here we show that a metamaterials approach, using a discrete physical geometry (conformation) of the segments of a polymer chain as the vector for a substantial refractive index change, can be used to enable visible wavelength, conjugated polymer photonic elements. In particular, we demonstrate that a novel form of dip-pen nanolithography provides an effective means to pattern the so-called β-phase conformation in poly(9,9-dioctylfluorene) thin films. This can be done on length scales ≤500 nm, as required to fabricate a variety of such elements, two of which are theoretically modelled using complex photonic dispersion calculations.